Bilateral Multiple Focal Choroidal Excavations in a Patient with Paroxysmal Nocturnal Hemoglobinuria (PNH) - Ping Huang; Tal Ben Ami; Weiye Li (Case Reports in Ophthalmological Medicine)
Focal choroidal excavation (FCE) is an unusual configuration characterized by focal thinning and pitting of the choroid in the absence of staphyloma or scleral ectasia. The etiology and clinical implications of FCE are currently unknown. We report a case of bilateral multiple FCEs in a patient with a long history of paroxysmal nocturnal hemoglobinuria (PNH). Focal choriocapillaris thinning and hyperreflectivity of the adjacent outer nuclear layer were revealed by spectral domain optical coherence tomography, which suggests the occlusion of the choriocapillaries and secondary degeneration of the above photoreceptors. We hypothesize that thrombophilia in the condition of PNH played an important role in the formation of FCE. Although there is no histopathological evidence to support the association between the choroid changes and PNH, this case may offer new clues as for the etiology of FCE.